2006
DOI: 10.1021/jp055243y
|View full text |Cite
|
Sign up to set email alerts
|

A SERS-Active System Based on Silver Nanoparticles Tethered to a Deposited Silver Film

Abstract: A series of SERS-active nanostructures were produced by exposing a freshly deposited silver film (fabricated to be as free from roughness as practicable) to a solution containing a mixture of 1-decanethiol (m) and 1,9-nonanedithiol (d) of varying concentrations of m to d, then allowing colloidal silver nanoparticles to interact with the surface. Silver nanoparticles were found to bind exclusively to films which were prepared from solutions with a nonzero concentration of the dithiol implying that the nanoparti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
91
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(98 citation statements)
references
References 50 publications
2
91
0
3
Order By: Relevance
“…Currently a variety of metallic and nonmetallic nanoparticles such as gold, alginate, silver, copper, zinc, titanium, magnesium, platinum and silica etc., are emerged. These nanoparticles are used in various fields such as optical devices (Anderson and Moskovits, 2006), catalytic (Jiang et al, 2005), bactericidal (Sekar et al, 2011), antibiofouling (Agarwal et al, 2014), dye degradation (Priyaragini et al, 2014), electronic (Rao et al, 2000), sensor technology (Sharpe and Andreescu, 2015), treatment of some cancers (Praetorius and Mandal, 2007) and malaria (Karthik et al, 2013). This wide range of application justifies the research and development inputs required in the field of nanotechnology.…”
Section: Introductionmentioning
confidence: 99%
“…Currently a variety of metallic and nonmetallic nanoparticles such as gold, alginate, silver, copper, zinc, titanium, magnesium, platinum and silica etc., are emerged. These nanoparticles are used in various fields such as optical devices (Anderson and Moskovits, 2006), catalytic (Jiang et al, 2005), bactericidal (Sekar et al, 2011), antibiofouling (Agarwal et al, 2014), dye degradation (Priyaragini et al, 2014), electronic (Rao et al, 2000), sensor technology (Sharpe and Andreescu, 2015), treatment of some cancers (Praetorius and Mandal, 2007) and malaria (Karthik et al, 2013). This wide range of application justifies the research and development inputs required in the field of nanotechnology.…”
Section: Introductionmentioning
confidence: 99%
“…Synthesis of silver nanoparticles is a significant area of research, because Ag nanoparticles have potential applications in various fields such as biochemistry, environment, medicine, catalysis, electronics and optics [1][2][3][4]. Particularly, the recent finding revealed that Ag nanoparticles can bind to the HIV [5].…”
Section: Introductionmentioning
confidence: 99%
“…Most recently, there is a global interest among the scientists to develop, improve, employ and use nanoparticles for solving various problems encountered by mankind. In recent past, a variety of metallic and non-metallic nanoparticles are extensively used in various fields such as pharmaceuticals, optical devices, catalyst, bioremediation, electronic and sensor technology (Praetorius et al, 2007;Karthik et al, 2013;Anderson et al, 2006;Jiang et al, 2005;Agarwal et al, 2014;Sharpe et al, 2014).…”
Section: Introductionmentioning
confidence: 99%